ANALISIS POTENSI SUMBER DAYA MANUSIA NAGARI PARIANGAN KABUPATEN TANAH DATAR - Vandy Fahrul; yurni suasti; febriandi . (JURNAL BUANA, 2017)
This study aimed to obtain data and information on the Potential Human Resources Nagari Pariangan Tanah Datar relating to (1) Population Density, (2) age, (3) Level of Education, (4) Livelihood Principal, (5) Religion and Beliefs, (6) Citizenship, (7) Ethnic and Tribal, and (8) Labor. This study was a descriptive study using secondary data analysis using scoring techniques. Research region includes Nagari Pariangan consisting of four ellipse that is, Guguak, Padang Panjang, Pariangan, and Sikaladi.Results of the study (1) Population Density more than 100 inhabitants / km2, (2) the age group of 25-50% of the population aged 18-56 years, (3) education level, age group 7-18 years are out of school less than 10%, the age group of 12-56 years who have never attended school less than 10%, the age group of 12-56 years do not complete primary school less than 10%, 12-56 years who had not completed junior high school each less than 30%, the age group 18-56 years who did not graduate from high school less than 15%, (4) Total distribution of basic livelihood livelihood range of 5-10 kinds of goods, largely residents of livelihood of farmers, ranchers, merchants, (5) religious distribution of the population, all the inhabitants of religion ISLAM, ( 6) Citizenship residents, all residents of an Indonesian citizen (citizen), (7) the intermingling of ethnic / tribal people, all residents are from one ethnic / tribal namely Minang tribe, (8) labor viewed from, the age group 18-56 years residents who do not work on average below 5%, the age group of 18-56 t ear who work more than 50%, whereas the number of work-age population dependency 18-56 years of working with people 0-56 years and over who did not work reaches 50-90%.